Note—Economic Ordering Frequency for Several Items Jointly Replenished - Nocturne, Dominique J. (Management Science, 1973)
We consider a problem typical of the batch processing industry. This problem arises when a product is packaged simultaneously into more than one type container after its manufacture, and when set-up costs are associated with the making of the product as well as the packaging of the various items. We formulate the production inventory problem so as to minimize the total holding and set-up costs and give a graphical solution for the two-item case.